The rural areas: sustainable development of residential buildings in relation to protected areas - Źróbek-Sokolnik, Anna; Zysk, Elżbieta; Dynowski, Piotr; Źróbek-Różańska, Alina (International Conference “Environmental Engineering”, 2017)
This paper aims to considering whether protected areas (in particular Natura 2000 areas) are barrier the development of housing opportunities in rural areas. Research in this area, based on the available Polish-language and English-language scientific papers, was conducted in the following aspects: legal, spatial and social. The case studies have shown situations in which the areas have been an incentive for a potential investor to settle in the area, and on the other hand, will identify aspects where legal restrictions may constitute a barrier to settle in the area. The above considerations were indicated for sustainable development, which should be the desired state for any space, including rural areas. Presented results and other literature data indicate therefore a positive impact of Natura 2000 areas on sustainable residential development in rural areas, including the development of the residential function.
Keywords: environmenatl protection; Natura 2000; rural areas; sustainable development